2021
DOI: 10.1590/s1517-707620210004.1370
|View full text |Cite
|
Sign up to set email alerts
|

Tannin quantification and chemical-energetic characterization of biomass residues of Bertholletia spp. and Lecythis’ spp. fruits

Abstract: Biomass residues originated from agroforestry systems has been demonstrating great usage potential for the pharmaceutical, textile and energy industries. In the Amazon region, the use of these materials can stimulate the sustainable economic development of extractive communities and agroforestry systems. However, for a better use of this material, it is necessary to quantify and qualify the chemical components present in these residues. Keeping that in mind, our research aimed to quantify the presence of conde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(40 reference statements)
2
0
0
Order By: Relevance
“…The contents found are close to what was found by [9], who obtained 73.20% using residues of orange tree pruning. Values similar to the present study were found for bean straw and corn cob (70.17 and 74.37%, respectively) according to [36], and lower values were found by [49] between 56.56 and 57.27% of holocellulose using Bertholletia excelsa (Brazil nut tree) and Lecythis pisonis (Castanheira-de-sapucaia), respectively. Holocellulose is of fundamental importance because the degradation of the molecules that compose it occurs in an extensive temperature range, approximately 150-450 • C, which gives thermal stability in the burning of biomass [52], although, according to [49], there is an inverse relationship with the fixed carbon content, which is corroborated by [44], who obtained higher levels of holocellulose and, consequently, lower levels of lignin by studying various wood residues.…”
Section: Chemical Characterizationsupporting
confidence: 90%
See 1 more Smart Citation
“…The contents found are close to what was found by [9], who obtained 73.20% using residues of orange tree pruning. Values similar to the present study were found for bean straw and corn cob (70.17 and 74.37%, respectively) according to [36], and lower values were found by [49] between 56.56 and 57.27% of holocellulose using Bertholletia excelsa (Brazil nut tree) and Lecythis pisonis (Castanheira-de-sapucaia), respectively. Holocellulose is of fundamental importance because the degradation of the molecules that compose it occurs in an extensive temperature range, approximately 150-450 • C, which gives thermal stability in the burning of biomass [52], although, according to [49], there is an inverse relationship with the fixed carbon content, which is corroborated by [44], who obtained higher levels of holocellulose and, consequently, lower levels of lignin by studying various wood residues.…”
Section: Chemical Characterizationsupporting
confidence: 90%
“…Ref. [49] found values close to the previous ones (27.64 and 23.30%) using residues of the fruit of Bertholletia excelsa (Brazil nut tree) and Lecythis pisonis (Castanheira-de-sapucaia), respectively. Ref.…”
Section: Chemical Characterizationsupporting
confidence: 78%